2020
DOI: 10.3390/rel11080419
|View full text |Cite
|
Sign up to set email alerts
|

Islam in Australia: A National Survey of Muslim Australian Citizens and Permanent Residents

Abstract: This article presents the findings of a national survey on Islam in Australia based on responses of 1034 Muslim Australian citizens and permanent residents. Knowing what Muslim Australians think about Islam in relation to Australian society is essential for a more informed understanding about Islam and Muslims needed to address misinformation, Islamophobia, and extremism. The findings presented in this article include typologies of Muslims; sources of influence concerning Islam; interpretations of the Qur’an; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…They were overwhelmingly supportive of the necessity for changes in the quality of women's spaces in the mosque. The poor quality of women's space in the mosque is well supported by current scholarship (Rane et al 2020;Shannahan 2014;Woodlock 2010b). Mosques that are open to women usually only offer them physical spaces which are poorer in quality and size compared to men's space.…”
Section: Views On Gender Segregationmentioning
confidence: 98%
See 3 more Smart Citations
“…They were overwhelmingly supportive of the necessity for changes in the quality of women's spaces in the mosque. The poor quality of women's space in the mosque is well supported by current scholarship (Rane et al 2020;Shannahan 2014;Woodlock 2010b). Mosques that are open to women usually only offer them physical spaces which are poorer in quality and size compared to men's space.…”
Section: Views On Gender Segregationmentioning
confidence: 98%
“…Current scholarship has found that mosques are significant places for Muslim women in Western contexts to gain knowledge about Islam, worship, improve their spirituality, engage with the Muslim community and gain a sense of belonging (Nyhagen 2019;Rane et al 2020;Shannahan 2014). For most of the women in the study, the main motivation and reason for attending the mosque were for worship and spirituality, as well as connecting with and belonging to the Muslim community.…”
Section: Motivation For Mosque Attendancementioning
confidence: 99%
See 2 more Smart Citations
“…These contributors represent many of Australia's universities engaged in Islamic and Muslim studies, including the Australian National University, Charles Sturt University, Deakin University, Griffith University and the University of Newcastle. The topics covered in this Special Issue include how Muslim Australians understand Islam (Rane et al 2020); ethical and epistemological challenges facing Islamic and Muslim studies researchers (Mansouri 2020); Islamic studies in Australia's university sector (Keskin and Ozalp 2021); Muslim women's access and participation in Australia's mosques (Ghafournia 2020); religion, belonging and active citizenship among Muslim youth in Australia (Ozalp and Cufurović 2021); responses of Muslim community organizations to Islamophobia (Cheikh Husain 2020); Muslim ethical elites (Roose 2020); and migration experiences of Hazara Afghans (Parkes 2020).…”
mentioning
confidence: 99%